Relationship of clinicopathological parameters and preoperative CA19-9 level in patients with gastric cancer - Shirin, Laila; Rahman, Md Mizanur; Ahmed, Saifuddin; Hossain, Md Nabir (Journal of Dhaka Medical College, 2015)
Objective: This study is an evaluation of serum level of the tumor marker CA 19-9 in gastric cancer patients in preoperative periods to assess the relationship of level of tumor markers in serum and clinicopathological parameters in gastric cancer. Methods: A prospective study was done of 61 patients diagnosed with gastric cancer treated at a single institution in Bangladesh National Institute of Cancer Research and Hospital (NICRH), Dhaka, from July 2010 to December 2011. Analyses were performed to identify patient and tumor-related characteristics in gastric cancer patients. The sera from 61patients with gastric cancer were measured for CA19-9 level using a commercial immunoradiometric assay. All the patients underwent diagnostic imaging with computed tomography (CT) or ultrasound (US) before laparotomy. Metastasis was confirmed by either by US or CT and direct visualization of metastatic deposits after laparotomy. Results: The serum levels of CA 19-9 e the cutoff value of 40 U/ml was regarded as positive. The serum levels of CA 19-9 d the cutoff value of 40 U/ml was considered as negative. Clinicopathological factors age, sex, tumor infiltration, N-classification, staging and grading was compared with CA19-9 level in gastric carcinoma. Preoperative levels of CA19-9 was above the cut-off levels in 23% of all cases. In the present study, we found CA 19-9 positivity was not significantly related with age (p.48) & sex (p.35) of the patients. There was no correlation with the histologic type and CA 19-9 positivity (P.19). CA 19-9 positivity had correlation with the proportions of depth of invasion (T stage) (P.007), lymph node involvement (P.000), metastasis (p .03); but no correlation with stage (P .4) in case of gastric carcinoma. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22696 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 60-67